Comparison of diagnostic performance between contrast-enhanced mammography and breast magnetic resonance imaging - Yang, Ying; Yang, Xiangying; Yang, Fan (Frontiers in Oncology, 2026)
ObjectiveContrast-enhanced mammography (CEM) is an emerging imaging technique. This study aims to compare the diagnostic accuracy of CEM and magnetic resonance imaging (MRI) for breast lesions.MethodsA retrospective analysis was conducted on patients who underwent both CEM and MRI at our institution from July 2019 to April 2024. All imaging reports were prepared in accordance with the Breast Imaging Reporting and Data System (BI-RADS) guidelines established by the American College of Radiology (ACR). The final diagnosis was established using pathology as the “gold standard.” The diagnostic performance of the two methods in detecting breast lesions was compared using sensitivity, specificity, accuracy, positive predictive value (PPV), negative predictive value (NPV), and receiver operating characteristic (ROC) curves.ResultsA total of 292 patients underwent paired CEM and MRI examinations, with an average age of 46.9 years. Among the 301 breast lesions identified, 121 (40.2%) were benign, and 180 (59.8%) were malignant. The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of CEM for diagnosing benign and malignant breast lesions were 98.9%, 78.5%, 90.7%, 87.3%, and 97.9%, respectively. The corresponding values for MRI were 98.9%, 72.7%, 88.4%, 84.4%, and 97.8%. No significant difference was observed in the diagnostic performance between the two methods (p > 0.05). The areas under the curve (AUC) for CEM and MRI were 0.887 (95% CI: 0.85–0.92) and 0.858 (95% CI: 0.81–0.90), respectively (p = 0.400).ConclusionAs an emerging imaging technique for detecting and diagnosing breast lesions, CEM demonstrates diagnostic performance comparable to that of MRI.